2019
DOI: 10.1021/acs.jpcc.9b10838
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Discontinuity at an Evaporating Water Interface

Abstract: Evaporative mass flux is governed by interfacial state of liquid and vapor phases. For closely similar pressures and mass fluxes of liquid water into its own vapor, discontinuity between interfacial liquid and vapor temperatures in the range of 0.14-28 K is reported. This controversial discontinuity has resulted in an obstacle on understanding and theoretical modeling of evaporation. Here, through study of vapor transport by Boltzmann transport equation solved through Direct Simulation Monte Carlo Method, we d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 49 publications
1
6
0
Order By: Relevance
“…These estimates and the ensuing conclusion are strongly supported by the close match between J sub values inferred from temperature scanning and the near-isothermal experiments . We also note that the results of the past TOF and more recent studies , also exclude the existence of large (e.g., >0.4 K) temperature “discontinuities” at the interface between condensed aqueous phases and their vapor.…”
supporting
confidence: 84%
“…These estimates and the ensuing conclusion are strongly supported by the close match between J sub values inferred from temperature scanning and the near-isothermal experiments . We also note that the results of the past TOF and more recent studies , also exclude the existence of large (e.g., >0.4 K) temperature “discontinuities” at the interface between condensed aqueous phases and their vapor.…”
supporting
confidence: 84%
“…They found that the heat conduction through the thermocouple wires can cause a large temperature measurement error in the vapor phase. Jafari et al obtained the same conclusion through Direct Simulation Monte Carlo Method. Therefore, the temperature discontinuity should be measured under a low heat flux from the vapor side.…”
Section: Resultsmentioning
confidence: 55%
“…Part of this discrepancy can also be attributed to the peculiarities that continue to be discovered about the structure of water, especially at the interfaces. [30][31][32][33] The correlation between the enthalpy of mixing (kcal/mol) versus the average chemical shift (ppm) for the (HNO 3 ) n (H 2 O) clusters is fair (Figure S3, R 2 =0.91) while the same correlation with the experimental data is also within acceptable limits (Figure S4, R 2 =0.90). With the limited data at hand, the relationship between enthalpies of mixing and chemical shifts can not be generalized at this stage.…”
Section: -Heat Of Mixing (Experimental and Calculated)mentioning
confidence: 63%